A threshold gap size for in situ secondary caries lesion development. (January 2019) - Maske, T.T.; Hollanders, A.C.C; Kuper, N.K.; Bronkhorst, E.M.; Cenci, M.S.; Huysmans, M.C.D.N.J.M
Abstract: Objectives: This study investigated the influence of very small gaps in secondary caries (SC) development and additionally linked the threshold gap size with the caries activity level from volunteers. Methods: For 21 days, 15 volunteers wore a modified occlusal splint loaded with dentin-composite samples restored with different interfaces: bonded (B = samples restored with complete adhesive procedure), no-bonded (NB = restored with composite resin without adhesive procedure), and 30, 60 and 90 μm (no adhesive procedure and with intentional gap). The splint was dipped in a 20% sucrose solution (10 min) 8 x per day. Samples were imaged with transversal wavelength independent microradiography (T-WIM) and lesion depth and mineral loss were calculated. Average wall lesion depth from each volunteer was determined and according to the values the volunteers were grouped as high, mid and low caries activity levels. Results: No wall lesion formation was observed in B and NB groups. In general, intentional gaps led to SC lesion depth progression independent of caries activity level of volunteers. No substantial wall lesions were found for two volunteers. A trend for deeper lesion in larger gaps was observed for the high activity group. Conclusion: Very small gaps around or wider than 30 μm develop SC independent of the caries activity level of the patient and SC wall lesion progression seemed to be related to individual factors even in this standardized in situ model. Significance: Independently of caries activity level of the patient, the threshold gap size for secondary caries wall lesion seems to be 30 μm at most.